2007
DOI: 10.1093/molbev/msm195
|View full text |Cite
|
Sign up to set email alerts
|

Human TRIM71 and Its Nematode Homologue Are Targets of let-7 MicroRNA and Its Zebrafish Orthologue Is Essential for Development

Abstract: Animal microRNAs (miRNAs) are short RNAs that function as posttranscriptional regulators of gene expression by binding to the target mRNAs. Noting that some miRNAs are highly conserved in evolution, we explored the possibility of evolutionary conservation of their targets. We identified human orthologues of experimentally verified let-7 miRNA target genes in Caenorhabditis elegans and used the luciferase reporter system to examine whether these human genes are still the targets of let-7 miRNA. We found that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 60 publications
3
59
0
Order By: Relevance
“…In C. elegans, let-7 triggers the rapid degradation of lin-41 mRNA at the L4-to-adult transition (50,51). lin-41 encodes a TRIM/RBCC family protein, homologous to human TRIM71 (52), that negatively regulates expression of LIN-29, a transcription factor required for adult cell fate specification (50). Depletion of alg-1 leads to significant derepression of lin-41 mRNA compared with empty vector RNAi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans, let-7 triggers the rapid degradation of lin-41 mRNA at the L4-to-adult transition (50,51). lin-41 encodes a TRIM/RBCC family protein, homologous to human TRIM71 (52), that negatively regulates expression of LIN-29, a transcription factor required for adult cell fate specification (50). Depletion of alg-1 leads to significant derepression of lin-41 mRNA compared with empty vector RNAi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Lin28b, we characterized the expression of the high mobility group transcription factor Hmga2, which has been shown to promote organismal growth and stemness in other systems (28,29). Similar to Lin28b, both human and murine Hmga2 harbor let-7 binding sites in their 3′ UTRs and are negatively regulated by the let-7 miRNAs (23,24,30,31). In the mammalian cochlea, prosensory cell differentiation follows a steep basal-to-apical gradient, whereby midbasally located HCs differentiate before more apically located HCs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to lin-28, let-7 was initially identified in C. elegans as a heterochronic gene (10,21). Let-7 miRNAs inhibit stem cell/ progenitor cell proliferation and promote differentiation by targeting cell cycle and growth-associated genes (22)(23)(24). The Lin28 genes possess multiple let-7 binding sites in their 3′ UTR and are subject to negative regulation by let-7 miRNAs, establishing a double negative feedback loop (19).…”
mentioning
confidence: 99%
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%